2008
DOI: 10.1007/s00438-008-0414-6
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial Tn9 chloramphenicol resistance gene: an attractive DNA segment for Mos1 mariner insertions

Abstract: The eukaryotic mariner transposons are currently thought to have no sequence specificity for integration other than to insert within a TA contained in a degenerated [TA](1-4) tract, either in vitro or in vivo. We have investigated the properties of a suspected hotspot for the integration of the mariner Mos1 element, namely the Tn9 cat gene that encodes a chloramphenicol acetyl transferase. Using in vitro and bacterial transposition assays, we confirmed that the cat gene is a preferential target for MOS1 integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…It contained the pBR322 tetracycline-resistance gene without its own promoter cloned between the XbaI and HindIII restriction sites of the multi-cloning site of the pBC vector, in reverse orientation to that of chloramphenicol and LacZ genes. Thus, it was unable to confer resistance to E. coli cells in tetracycline concentrations over 10 g/ml (Crénès et al 2009). This gene was Xanked by two 3ЈITR cloned between KpnI/ SacI and SalI/NotI sites.…”
Section: Transposon Donors With Variable Itrsmentioning
confidence: 99%
“…It contained the pBR322 tetracycline-resistance gene without its own promoter cloned between the XbaI and HindIII restriction sites of the multi-cloning site of the pBC vector, in reverse orientation to that of chloramphenicol and LacZ genes. Thus, it was unable to confer resistance to E. coli cells in tetracycline concentrations over 10 g/ml (Crénès et al 2009). This gene was Xanked by two 3ЈITR cloned between KpnI/ SacI and SalI/NotI sites.…”
Section: Transposon Donors With Variable Itrsmentioning
confidence: 99%
“…Indeed, the effects of supercoiling on the rate of mariner transposition and target site selection have been previously noted (11,18,20). However, one might reasonably wonder about the biological significance of these observations.…”
mentioning
confidence: 95%
“…We demonstrated here for the first time that the TA dinucleotide plays a crucial role in target capture and DNA strand transfer. Previous studies revealed that the local DNA sequences immediately surrounding the TA dinucleotide confer little target specificity, although they show a slight preference for TA dinucleotides that are flanked by A-T base pairs (10,22,23). It is tempting to imagine that the bending of the TA-rich targets is energetically more favorable for setting up the strand transfer reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some elements have specific (attTn7 for Tn7) (13) or preferred (HisG1 for Tn10, G(CT)(CT) (CT)(AT)(AG)(AG)(AG)C for Tn5) (20,21) targets, whereas mariner elements display an essentially random integration pattern. However, it has been shown that Mos1 may have preferred integration spots such as the one in the chloramphenicol resistance gene of Tn9 (22). No structural features explaining the preferential integration of Mos1 have yet been identified (23).…”
mentioning
confidence: 99%